(untitled) (CIPEEX, 2025)
The project developed for Cristal Frios involves the creation of an advanced Data Analysis and Reporting solution, focused on wholesale and retail operations of cold products. This system is designed to integrate and analyze inventory and sales data, offering a robust tool for efficient inventory management and strategic decision-making. Through the collection and processing of critical data, the system generates detailed reports that provide valuable insights into product performance, demand patterns, and market trends. The solution applies data analysis techniques to optimize inventory levels, minimize waste, and adjust purchasing strategies according to demand. Additionally, it allows continuous monitoring of operations, facilitating the identification of improvement opportunities and quick responses to market changes. The system is designed to provide an intuitive interface that simplifies data visualization and interpretation, supporting the company in maintaining its competitiveness and operational efficiency. This project demonstrates the practical application of data analysis and reporting concepts, contributing to improved business management and informed decision-making.